2010
DOI: 10.3834/uij.1944-5784.2010.06.03
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Changes in Patients Undergoing Hemodialysis

Abstract: Abbreviations and AcronymsECG = electrocardiography or electrocardiogram QRS-c = QRS complex QTc = QT interval corrected for heart rate QTD = QT dispersion ABSTRACT INTRODUCTION: Patients with end-stage renal disease who are on long-term dialysis support have a very high mortality. Nearly half of deaths on dialysis are secondary to myocardial infarction, cardiac arrest, malignant arrhythmias, and other cardiac causes. The purpose of the present study was to compare electrocardiogram (ECG) disturbances before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…Beyond that, studies that use continuous monitoring such as Holter monitoring instead of ECG recordings at specific time points should be considered. There was also a slight increase of QRS duration at peak stress during HD, in agreement with the results of Salari et al [ 26 ]. Evidence has shown that in both ischemia cardiomyopathy patients and non-ischemia cardiomyopathy patients, abnormal intraventricular conduction is a risk factor for mortality and sudden death [ 27 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Beyond that, studies that use continuous monitoring such as Holter monitoring instead of ECG recordings at specific time points should be considered. There was also a slight increase of QRS duration at peak stress during HD, in agreement with the results of Salari et al [ 26 ]. Evidence has shown that in both ischemia cardiomyopathy patients and non-ischemia cardiomyopathy patients, abnormal intraventricular conduction is a risk factor for mortality and sudden death [ 27 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Changes in plasma Na, K, and ionized Ca in HD have significant effects on QTcd. 28 Electrocardiogram data demonstrate that the risk of arrhythmia could be higher with decreased plasma Na, K, and decreased ionized Ca during HD. 29 A study showed that hemodialysis increases the QTc interval in ESRD patients, mainly because of rapid changes in plasma electrolyte concentrations 16,30 ; another study indicated that there was no correlation between the changes in QTd and the changes in serum cations.…”
Section: Discussionmentioning
confidence: 99%